2015
DOI: 10.1017/s0033291715000057
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neurocognitive functioning during transition to manifest disease: comparison of individuals at risk for schizophrenic and bipolar affective psychoses

Abstract: Our data provide no evidence for a progressive cognitive decline in individuals at risk of psychosis. In line with the neurodevelopmental model, our findings suggest that cognitive deficits are already present very early, before or during the prodromal stage of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 71 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…In contrast, a recent study showed that 10 prodromal individuals at clinical high risk for BD had non-significantly better baseline performance compared to both the 60 clinical high-risk SZ individuals and the 12 individuals converting to SZ during the 1 year follow-up. 27 However, as the group of 4 individuals who converted to BD were not included in the analysis, it is unknown whether cognitive performance in these individuals was impaired before or after the transition.…”
Section: Cognitive Functioning Pre-onset and In Cohorts At Familialmentioning
confidence: 99%
“…In contrast, a recent study showed that 10 prodromal individuals at clinical high risk for BD had non-significantly better baseline performance compared to both the 60 clinical high-risk SZ individuals and the 12 individuals converting to SZ during the 1 year follow-up. 27 However, as the group of 4 individuals who converted to BD were not included in the analysis, it is unknown whether cognitive performance in these individuals was impaired before or after the transition.…”
Section: Cognitive Functioning Pre-onset and In Cohorts At Familialmentioning
confidence: 99%
“…People with SMI are also at increased risk of various other physical comorbidities, such as respiratory disease [12, 13], poor bone health [14] and physical multimorbidity [15]. Moreover, people with SMI typically experience pronounced cognitive impairment, which often worsens over time [1618] and for which treatment approaches remain limited [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairments are usually evaluated using neuropsychological batteries, which assess memory, attention and related cognitive functions. The cognitive disorders are found to more or less preexist the clinical pathology, and persist after the onset of schizophrenia symptoms without any large variation ( Becker et al, 2010 ; Nuechterlein et al, 2014 ; Bora and Murray, 2015 ; Metzler et al, 2015 ; Bergh et al, 2016 ; but see Zhou et al, 2017 ). Moreover, they predict the functional outcome of the patients ( Lewandowski et al, 2013 ; Green, 2016 ; Thomas et al, 2017 ), but it is not clear how they relate with clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%